Spontaneous regression of bone marrow hypoplasia associated with skin manifestations of myeloid leukemia. - Santoro, N.; Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Specific cutaneous leukemic lesions are present in 1% of cases, more frequently (5%) in acute, non lymphoblastic leukemia (1). The skin lesions may precede the blood and bone marrow manifestations and disappear with the appearance of the circulating blasts (4). The case here reported is peculiar due to the presence of specific cutaneous lesions of myeloid leukemia in absence of blood manifestations, but associated with severe bone marrow hypoplasia. Although exceptionally, cases of specific leukemic cutaneous lesions were reported, not preceded nor followed by blood manifestations (3). In a 6-month-old boy specific leukemic skin lesions associated with cutaneous mastocytosis but with-out blood manifestations were reported (2). In the latter case the specific leukemic cutaneous lesions regressed spontaneously within 6 months simultaneously to spontaneous regression of mastocytosis (2).